ETIOLOGICAL STRUCTURE AND ECOLOGICAL SIGNIFICANCE OF OPPORTUNISTIC PATHOGENS IN BRONCHITIS - Kovalenko, N.I.; Zamaziy, T.M.; Novikova, I.V.; Taranenko, G.P. (World of Medicine and Biology, 2020)
The study of microecological indices of the microflora in patients with bronchitis revealed the spread of endogenous bacteria of the nasal pharynx in the bronchi biocenosis, which was confirmed by constancy index and Berger-Parker index of dominance. The etiological spectrum of infectious factors was dominated by viridans group streptococci and fungi of the genus Candida, which had a high colony-forming level. Microorganisms were inoculated in both monocultural and communities form, which numbered from two to four species. The most common were combinations of bacteria and fungi of the genus Candida, which were recorded in 62.7% (64/102). The communities included not only autochthonous bacteria, but also such uncharacteristic for biotope as K. pneumoniae, P. aeruginosa, E. coli, E. cloacae, E. aerogenes, E. faecalis, E. faecium.
Keywords: opportunistic pathogens; bronchitis